EFFECT OF TOTAL ASSET TURNOVER, CASH FLOW, GCG, PROFITABILITY AGAINST FINANCIAL DISTRESS CASH HOLDING AS MODERATION - Kismanah, Imas; Kimsen, Kimsen; Utomo, Eko Narto (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of Total Asset Turnover, Cash Flow, Good Corporate Governance, and Profitability through Cash Holding as Moderation on Financial Distress. The research time period was during 2018 – 2022. The population of this study included manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sampling technique employed purposive sampling technique. Based on the criteria, 24 company samples were obtained. The type of data used secondary data obtained from the official website of the Indonesia Stock Exchange. The data analysis method used panel data regression analysis. The results revealed that Total Asset Turnover and Good Corporate Governance partially had an influence on financial distress, Cash Flow and Profitability partially had no influence on financial distress, Cash Holding partially had no influence on financial distress. Cash Holding which moderates Total Asset Turnover and Good Corporate Governance shows results that it can strengthen the correlation to financial distress. Meanwhile, Cash Holding moderating Cash Flow and Profitability cannot strengthen the correlation to Financial Distress.Keywords: Total Asset Turnover, Cash Flow, Good Corporate Governance, Profitability, Cash Holding, Financial Distress.